Liver Angiopoietin‐2 Is a Key Predictor of DeNovo or Recurrent Hepatocellular Cancer After Hepatitis C Virus Direct‐Acting Antivirals. Issue 3 (15th September 2018) - Faillaci, Francesca; Marzi, Luca; Critelli, Rosina; Milosa, Fabiola; Schepis, Filippo; Turola, Elena; Andreani, Silvia; Vandelli, Gabriele; Bernabucci, Veronica; Lei, Barbara; D'Ambrosio, Federica; Bristot, Laura; et al.
Abstract : Recent reports suggested that direct acting antivirals (DAAs) might favor hepatocellular carcinoma (HCC). In study 1, we studied the proangiogenic liver microenvironment in 242 DAA‐treated chronic hepatitis C patients with advanced fibrosis. Angiopoietin‐2 (ANGPT2) expression was studied in tissue (cirrhotic and/or neoplastic) from recurrent, de novo, nonrecurrent HCC, or patients never developing HCC. Circulating ANGPT2, vascular endothelial growth factor (VEGF), and C‐reactive protein (CRP) were also measured. In study 2, we searched for factors associated with de novo HCC in 257 patients with cirrhosis of different etiologies enrolled in a dedicated prospective study. Thorough biochemical, clinical, hemodynamic, endoscopic, elastographic, and echo‐Doppler work‐up was performed in both studies. In study 1, no patients without cirrhosis developed HCC. Of 183 patients with cirrhosis, 14 of 28 (50.0%) with previous HCC recurred whereas 21 of 155 (13.5%) developed de novo HCC. Patients with recurrent and de novo HCCs had significantly higher liver fibrosis (LF) scores, portal pressure, and systemic inflammation than nonrecurrent HCC or patients never developing HCC. In recurrent/ de novo HCC patients, tumor and nontumor ANGPT2 showed an inverse relationship with portal vein velocity (PVv; r = –0.412, P = 0.037 and r = –0.409, P = 0.047 respectively) and a positive relationship with liver stiffness (r = 0.526, P = 0.007; r = 0.525, P = 0.003 respectively). Baseline circulating VEGF and cirrhotic liver ANGPT2 were significantly related (r = 0.414, P = 0.044). VEGF increased during DAAs, remaining stably elevated at 3‐month follow‐up, when it significantly related with serum ANGPT2 (r = 0.531, P = 0.005). ANGPT2 expression in the primary tumor or in cirrhotic tissue before DAAs was independently related with risk of HCC recurrence (odds ratio [OR], 1.137; 95% confidence interval [CI], 1.044‐1.137; P = 0.003) or occurrence (OR, 1.604; 95% CI, 1.080‐2.382; P = 0.019). In study 2, DAA treatment (OR, 4.770; 95% CI, 1.395‐16.316; P = 0.013) and large varices (OR, 3.857; 95% CI, 1.127‐13.203; P = 0.032) were independent predictors of de novo HCC. Conclusion: Our study indicates that DAA‐mediated increase of VEGF favors HCC recurrence/occurrence in susceptible patients, that is, those with more severe fibrosis and splanchnic collateralization, who already have abnormal activation in liver tissues of neo‐angiogenetic pathways, as shown by increased ANGPT2. (Hepatology 2018; 00:000‐000).